Experiments and modelling in N2-H2 capacitively coupled radio-frequency discharges at low pressure - Marques, L. (2013)
This work uses experiments and simulations to analyze the modifications induced in pure N2 capacitively coupled radio-frequency discharges, running at low pressure (0.6–1.2 mbar) and low power (5–20 W), by the addition of small amounts of H2 (up to 5%). Simulations use a hybrid code coupling a two-dimensional time-dependent fluid module, describing the dynamics of the charged particles, to a zero-dimensional kinetic module, describing the production and destruction of nitrogen and hydrogen neutral species. The discussion is particularly focused on the results obtained for the electron density and the radiative transition intensities with nitrogen species. Model predictions are in qualitative agreement with measurements, for the evolution of these quantities with changes in both the gas pressure and the hydrogen percentage in the gas mixture.